Good Corporate Governance Optimizing Community Awareness in the Distribution of ZIS - Khatimah, Husnul; Idris, Mahsyar; S, Andi Bahri; Semaun, Syahriyah; Suarning, Suarning (Universitas Muhammadiyah Makassar, 2025)
This study examines how the implementation of Good Corporate Governance (GCG) principles enhances community awareness in the distribution of Zakat, Infaq, and Sadaqah (ZIS) through ZIS management literacy at BAZNAS Enrekang Regency, Indonesia. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews, observation, and documentation involving BAZNAS administrators, sub-district zakat collection units (UPZ), muzakki (donors), and mustahik (beneficiaries). The results reveal that BAZNAS Enrekang applies GCG principles—transparency, accountability, responsibility, independence, and fairness—in managing ZIS funds. Transparency is realized through regular financial reporting and open access to information, while accountability is ensured by internal and external audits. However, limited community literacy regarding ZIS management reduces understanding and participation in zakat programs. To overcome this, BAZNAS conducts literacy campaigns, simplifies financial information, and involves muzakki in verification and distribution processes. The findings highlight that strengthening GCG-based literacy programs is essential to increase public trust, awareness, and active involvement in ZIS distribution. This study contributes to the literature on Islamic social finance governance by linking corporate governance mechanisms with public literacy and engagement outcomes.